THE IMPORTANCE OF THE APPLICATION OF FAIR VALUE OF THE COMPANY'S PROPERTY IN TRANSITIONAL COUNTRIES ON THE WAY TO THE EU - ČOLOVIĆ MRĐAN; JAKOVLJEVIĆ SANJA; BOGDAN LABAN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2018)
The fair value within the business improvement in the enterprises of the Republic of Serbia is continuing demanding work that is carried out in the framework of financial reporting management companies, sectors of economy, but the national authorities may require a completely evaluation of companies, based on the decisions of state bodies and individual requirements. An important place in this context have the internal audit, external audit, as these can be a driver of the fair value of the initial phase by the management council. External audit is able to thinking management delivered only after the end of the business year, when it receives the financial statements of the previous year of business, and then can make recommendations, because through their impact on future business management, provided that it is adopted, it will be is maintained in the next period of operation. Therefore regardless of the drivers and the initiator of the fair value now exist ways to increase the security of the overall business, and in this paper highlighted the fair value as an element of financial reporting. It is expected to increase the number of effective fair value in the Republic of Serbia, because companies can realize numerous benefits.